Relative fitnes of herbicide-resistant and susceptible biotypes of weeds - Warwick, S.I.; Black, L.D. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1994)
In recent years, there has been a rapid increase in the number of reported cases of herbicide-resistant weed species (over 100), as well as an increase in the types of herbicides to which resistance has evolved. This paper reviews evidence for differential fitness of herbicide-resistant and susceptible biotypes. Fitness estimates are required to produce reliable population models. Fitness measures describe the potential evolutionary success of a genotype based on survival, competitive ability and ultimately reproductive success. Differences in relative fitness between resistant and susceptible biotypes are usually inferred from measures of relative plant productivity or competitiveness. For triazine-resistant weed species, studies have indicated that resistant plants were generally less fit than susceptible plants, although exceptions did exist. Although less data are available on the fitness of plants resistant to non-triazine herbicides, information is summarized for sulfonylureas, substituted ureas, dinitroanilines, paraquat, diclofop, and organic arsenicals. No consistent differences in relative fitness were observed for non-triazine resistant and susceptible biotypes. In general, studies have indicated that the relative fitness of susceptible and resistant biotypes of a single species depends upon biological conditions, including genotype and population variation, intra- and inter-biotype competition, and environmental conditions such as temperature, light quality, and management practices. Future needs for relative fitness studies are discussed.